Anti-Money Laundering Regime in Pakistan; Deficiencies and A Way Forward - Cheema, Zaheer Iqbal; Cheema, Muhammad Arshad (Law and Policy Review, 2022)
The Financial Action Task Force (FATF) has placed Pakistan in the grey list for falling short of efforts to curb money laundering. Resultantly, Pakistan has been subject to increased monitoring regarding money laundering, terror financing and proliferation financing and encounters an enhanced follow-up. In the context of FAFT’s placement of Pakistan in the grey list and the measures taken by the Pakistani government to tackle money laundering, this study examines the efficacy of the legal regime regarding Anti-Money Laundering (AML) practices in Pakistan. It analyses critically the legal framework of Pakistan concerning AML and evaluates the policies adopted to combat it. The study argues that despite the commendable efforts of successive Pakistani governments to control money laundering, effective execution and capacity building of concerned institutions can play an important role in strengthening the domestic mechanism that counters/ prevent money laundering.